Penerapan Metode Pembelajaran Team Games Tournament Berbantuan Media Wordwall dalam Pembelajaran Teks Cerpen - Yuniarti, Indah; Ika Septiana; Susilowati (Edukasi Lingua Sastra, 2024)
The aim of this research is to describe the application of the Team Games Tournament learning method assisted by wordwall media in learning short story texts for class IX students at SMP Negeri 6 Semarang. This type of research is mixed. Information was collected through an evaluation method which included testing and assessment without testing. The test technique is in the form of questions describing the analysis of linguistic characteristics and the non-test technique is in the form of observation during the learning process and documentation. Triangulation is used to analyze research data. Presentation of the results of data analysis is carried out formally and informally. The results of this research show that the application of the Team Games Tournament learning method using wordwall media as a tool can significantly increase students' academic achievement, motivation and interest in learning. This is proven by the learning results of students with the lowest score of 80 and the highest score of 100. Overall, the learning results show that all students achieved complete information on KKTP with an average of 89.5. Referring to the results of test and non-test data analysis, it can be concluded that the Team Games Tournament learning method assisted by wordwall open the box media can be implemented in learning short story texts.